Standard care versus protocol based therapy for new onset Pseudomonas aeruginosa in cystic fibrosis. Issue 10 (2nd July 2013) - Mayer‐Hamblett, Nicole; Rosenfeld, Margaret; Treggiari, Miriam M.; Konstan, Michael W.; Retsch‐Bogart, George; Morgan, Wayne; Wagener, Jeff; Gibson, Ronald L.; Khan, Umer; Emerson, Julia; Thompson, Valeria; Elkin, Eric P.; et al.
Abstract Rationale The Early Pseudomonal Infection Control (EPIC) randomized trial rigorously evaluated the efficacy of different antibiotic regimens for eradication of newly identified Pseudomonas (Pa) in children with cystic fibrosis (CF). Protocol based therapy in the trial was provided based on culture positivity independent of symptoms. It is unclear whether outcomes observed in the clinical trial were different than those that would have been observed with historical standard of care driven more heavily by respiratory symptoms than culture positivity alone. We hypothesized that the incidence of Pa recurrence and hospitalizations would be significantly reduced among trial participants as compared to historical controls whose standard of care preceded the widespread adoption of tobramycin inhalation solution (TIS) as initial eradication therapy at the time of new isolation of Pa. Methods Eligibility criteria from the trial were used to derive historical controls from the Epidemiologic Study of CF (ESCF) who received standard of care treatment from 1995 to 1998, before widespread availability of TIS. Pa recurrence and hospitalization outcomes were assessed over a 15‐month time period. Results As compared to 100% of the 304 trial participants, only 296/608 (49%) historical controls received antibiotics within an average of 20 weeks after new onset Pa. Pa recurrence occurred among 104/298 (35%) of the trial participants as compared to 295/549 (54%) of historical controls (19% difference, 95% CI: 12%, 26%, P < 0.001). No significant differences in the incidence of hospitalization were observed between cohorts. Conclusions Protocol‐based antimicrobial therapy for newly acquired Pa resulted in a lower rate of Pa recurrence but comparable hospitalization rates as compared to a historical control cohort less aggressively treated with antibiotics for new onset Pa. Pediatr Pulmonol. 2013; 48:943–953. © 2013 Wiley Periodicals, Inc.